Academic Application at STIEM Bongaya Makassar Web-Based - Usman Usman; Sitti Harlina (Universitas Raharja, 2021)
This study aims to design a web-based academic information system at STIEM Bongaya Makassar. During this academic service to students is still done manually, for example at the end of the semester students usually queue up to see grades and class schedules that use paper media that is posted on the bulletin board, so servants to students become ineffective and inefficient. With the advancement of information technology such as internet media, it can support the academic activities of a college. So with the use of internet media students do not need to come directly to the lecture to get academic information The web-based academic information system at STIEM Bongaya Makassar is expected to provide convenience in managing student data and academic services. This academic information system will later be web-based created using the Php and MySQL programming languages ​​as a database, and white box testing as a testing method to find out whether an application has been made free of logical errors